CEO Hubris and Firm Pollution: A Tricky Relationship - Maximilian H. Theissen; Hubertus H. Theissen (Journal of Business Ethics, 2020)
This article comments on the recent study “CEO hubris and firm pollution: state and market contingencies in a transitional economy” of Zhang et al. (J Bus Ethics 161(2):459–478, 2020) in this journal. We very much appreciate the valuable initiative of Zhang et al. to study the potential effect of CEO characteristics on corporate pollution. At the same time, we are concerned with the authors' interpretation of the regression results and their operationalization of CEO hubris. We hope to contribute to the literature on managerial hubris in two ways. First, we repair the authors' inferences and conclusions about the actual effect of CEO hubris on firm pollution with respect to their conflicting regression results. Second, we unpack and clarify the authors' vulnerable operationalization of CEO hubris. We hope to stimulate more research on (1) the (tricky) relationship between CEO hubris and firm pollution, and (2) managerial hubris more generally through a more rigorous operationalization and measurement of hubris.
Keywords: 300; CEO hubris; Firm pollution; Operationalization of CEO hubris; Measurement of CEO hubris